SAT0101 Das does not predict increasing treatment in early rheumatoid arthritis (ERA): Results from the catch study. (23rd January 2014) - Pyne, L.; Bykerk, V.; Hitchon, C.; Keystone, E.; Thorne, C.; Boire, G.; Haraoui, B.P.; Bonner, A.; Pope, J.
Abstract : Background: The disease activity score (DAS) was developed in RA to guide therapy. Its utility in practice for ERA has not been fully studied. Objectives: The aim was to determine factors most strongly associated with an increase in therapy in ERA at 3 and 6 months. Methods: Data were collected from Canadian Early Arthritis Cohort (CATCH) patients who were included if they had ≥2 visits and baseline and 6 months data. A regression analysis determined factors associated with treatment intensification. Results: Of the 1, 145 ERA patients, 790 met inclusion criteria. Mean age was 53.4 (SD 14.7), disease duration 6.1 months (SD 2.8), 75% were female, baseline DAS28 was 4.7 (SD 1.8) and 2.9 (SD 1.8) at 6 months. Factors most strongly associated with intensifying treatment in univariate analyses were MD global (assessment) (OR=7.8 at 3 months and OR=7.4 at 6 months, P<0.0005) and SJC (OR=4.7 and OR=7.3 at 3 and 6 months, P<0.0005). DAS did not affect treatment intensification as strongly in univariate analyses (OR=3.0 at 3 months and OR=4.6 at 6 months, P<0.0005). In the logistic regression model only MD global was consistently associated with treatment intensification (OR=1.5 and OR=1.2 at 3 and 6 months respectively, P<0.0005). DAS28 was not a consistent predictor of treatment intensification (OR=1.0, P=0.987 at 3 months and OR=1.2 P=0.023 at 6 months). If adjusting for multiple comparisons, only MD global was significant at both 3 and 6 months. When treatment was intensified; only 2% of physicians listed DAS28 as a reason for the treatment change, compared to 52%, 50% and 24% for SJC, TJC and MD global respectively. For the same SJC, larger joint involvement was more likely to influence treatment than small joint involvement at 3 months (OR=1.4, P=0.027). At 3 (but not 6) months for the same joint count, larger joint involvement was more associated with increasing therapy (P=0.027). Summary of variables in logistic regression model of increase therapy (strict definition) at 3 and 6 months. Model had a percent correct classification of 76.2% and P-value <0.0005 at 3 months and 79.3% and P-value <0.0005 at 6 months. Conclusions: Physician global assessment was independently associated with an increase in treatment at 3 and 6 months in ERA, whereas DAS28 was only significant at 6 months. SJC was also strongly related to treatment intensification at 6 months. Physicians rarely stated that DAS28 was the reason for increasing treatment and the data demonstrate that MD global assessment (which is not part of the DAS) is the main reason for treatment intensification in ERA. Disclosure of Interest: L. Pyne Grant/Research support from: Canadian Rheumatology Association Roche Summer Studentship, JUMP CIHR Training Grant, V. Bykerk: None Declared, C. Hitchon: None Declared, E. Keystone: None Declared, C. Thorne: None Declared, G. Boire: None Declared, B. Haraoui: None Declared, A. Bonner: None Declared, J. Pope Grant/Research support from: The CATCH study was designed by the investigators and financially supportedby Amgen Canada and Pfizer Canada and as of 2011, further support was provided by Hoffmann-La Roche, United Chemicals of Belgium (UCB) Canada, Bristol-Myers Squibb Canada, Abbott Laboratories, and Janssen Biotech Inc. (a subsidiary of Johnson & Johnson Inc.).